2010
DOI: 10.1038/ja.2010.28
|View full text |Cite
|
Sign up to set email alerts
|

NBRI17671, a new antitumor compound, produced by Acremonium sp. CR17671

Abstract: The interaction between the receptor for advanced glycation end-product (RAGE) and amphoterin has an important role in tumor growth and metastasis. Because the abrogation of the interaction results in the inhibition of the tumor growth and metastasis, we designed a screening system for an inhibitor of the interaction between RAGE and amphoterin. In the course of our screening of the inhibitor, we isolated a novel natural compound NBRI17671 (1) from the fermentation broth of Acremonium sp. CR17671. We also modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…RAGE also interacts with amphoterin, which contributes to tumor growth and metastasis (29). Compound NBRI17671 (2) is a RAGE inhibitor that downregulates MAPK activity and effectively inhibits the growth of lung tumor xenografts in mice (30). This phenomenon maybe attributed to the blockade of RAGE-amphoterin.…”
Section: Receptors and Regulationmentioning
confidence: 99%
“…RAGE also interacts with amphoterin, which contributes to tumor growth and metastasis (29). Compound NBRI17671 (2) is a RAGE inhibitor that downregulates MAPK activity and effectively inhibits the growth of lung tumor xenografts in mice (30). This phenomenon maybe attributed to the blockade of RAGE-amphoterin.…”
Section: Receptors and Regulationmentioning
confidence: 99%
“…CR17671. It inhibits the interaction between Receptor for Advanced Glycation End products (RAGE) and amphoterin to induce antitumor effect (Kawada et al, ). Rue extract is also known to cause cell death by promoting AKT and ERK1/2 pathways in A1 cells.…”
Section: Natural Product and Glioma Therapymentioning
confidence: 99%
“…Ceramide may also function as an intracellular messenger in a lipid signal transduction pathway implicated in several processes linked to cell differentiation, apoptosis, and cell proliferation . A recent study has identified the natural metabolite NBRI17671 ( 3 ) and the reduced derivative 4 as novel inhibitors of the interaction of RAGE (receptor for advanced glycation end-product) and amphoterin . Blocking the interaction of RAGE and amphoterin results in an inhibition of tumor growth, motility, and angiogenesis …”
mentioning
confidence: 99%
“…4 A recent study has identified the natural metabolite NBRI17671 (3) and the reduced derivative 4 as novel inhibitors of the interaction of RAGE (receptor for advanced glycation end-product) and amphoterin. 5 Blocking the interaction of RAGE and amphoterin results in an inhibition of tumor growth, motility, and angiogenesis. 6 Cytosporic acid (5) has similar structural features and has been shown to inhibit HIV-1 integrase, an enzyme essential for viral replication.…”
mentioning
confidence: 99%